Response of benthic macroinvertebrates to different hydropower off‐stream diversion schemes. Issue 5 (13th December 2020) - Quadroni, Silvia; Salmaso, Francesca; Gentili, Gaetano; Crosa, Giuseppe; Espa, Paolo
Abstract: Despite significant advancement in environmental flow science, the release of minimum flows (MFs) still represents one of the main measures globally adopted to mitigate off‐stream diversion in regulated rivers. In the Lake Como basin (Italy), we monitored water‐depleted reaches below hydropower reservoirs and intakes and reaches unimpacted by water withdrawal. Our aim was to verify if the gradient in streamflow alterations resulted in detectable differences in the structure and functions of benthic assemblages, possibly identifying streamflow metrics explaining the observed differences. The macroinvertebrate assemblages sampled below reservoirs showed significant differences from those from unimpacted reaches, including the reduced relative richness of Ephemeroptera, Plecoptera and Trichoptera (mainly stoneflies) and the higher abundance and richness of dipterans. These differences were well explained by the corresponding streamflow pattern, characterized by a rather constant flow throughout the year, occasionally interrupted by sharp peaks related to spilling episodes. In contrast, the shift from unimpacted conditions was minor for benthic assemblages collected at reaches below intakes, where the seasonal streamflow variation was partly preserved. Our results suggest that an increase of the e‐flow released by hydropower dams during the seasons characterized by larger run‐offs could support improved benthic assemblages. Dewatered river sections below reservoirs could thus be prioritized for updating the current MF management, in the study area as well as in comparable contexts. At least to our knowledge, specific investigations are so far unavailable regarding the exploration of the different responses of benthic macroinvertebrates to intakes and reservoirs operations.